Neuronal Intranuclear Inclusion Disease: A Confirmed Case Report and Analysis of MRI Characteristics in Three Typical Cases - Liu, Jin; Zhang, Chuan; Wang, Jiwu; Yang, Hanfeng (Current Medical Imaging, 2025)
Objective: Neuronal Intranuclear Inclusion Disease (NIID) is a rare and clinically heterogeneous neurodegenerative disorder leading to diagnostic challenges. This study aims to investigate the clinical and characteristic radiological features of four adult female patients, offering insights into the clinical and radiological heterogeneity of NIID and its misdiagnosis potential.Case Representation: This case study presents a retrospective analysis of clinical data from four adult female patients, including one confirmed case and three with typical Magnetic Resonance Imaging (MRI) manifestations. The high signal intensity patterns on Diffusion-Weighted Imaging (DWI) and Fluid-Attenuated Inversion Recovery (FLAIR) sequences were reviewed in focus.Discussion: All four patients were adult females with common symptoms of NIID, such as recurrent headaches, cognitive decline, and autonomic dysfunction, accompanied by symptoms like vomiting, slowed responses, behavioral changes, and focal neurological symptoms. Genetic testing revealed a NOTCH2NLC gene mutation with GGC>113 repeats in one patient. Three patients from the same family presented with headaches, followed by vomiting and progressive unresponsiveness with two of them exhibiting abnormal behavior and one experiencing weakness and pain in the right limbs. Neurological assessments revealed peripheral neuropathy and intermittent confusion, among other manifestations. MRI features of all four patients were consistent with NIID, displaying high signals at the corticospinal junction on DWI and FLAIR sequences, with one case involving the vermis of the cerebellum.Conclusion: This case report enhances our understanding of NIID's diverse clinical phenotypes and the critical role of advanced MRI and genetic testing in its diagnosis. The core imaging feature of NIID is the high signal along the corticospinal junction on MRI, which, combined with NOTCH2NLC gene testing, can significantly enhance the early recognition and diagnosis of NIID. Therefore, this study deepens our understanding of the complex clinical phenotypes and imaging characteristics of NIID, providing crucial guidance for clinical practice.
Keywords: Neuronal intranuclear inclusion disease